Health-related quality of life of type 2 diabetes mellitus patients: a study in some selected hospitals in Malaysia / Zeinab Jannoo - Jannoo, Zeinab (2016)
This thesis presents the work on modelling Quality of Life (QoL) among Type 2 Diabetes Mellitus (T2DM) through the development of a Structural Equation Model (SEM). The motivation behind this research is influenced by several factors. Firstly, T2DM is an alarming global health issue and this has lead interest among researchers and healthcare providers to find ways to reduce the T2DM prevalence. Secondly, the effect of T2DM is known to affect HRQoL of patients and although intervention measures have been implemented, significant results have yet to be achieved. An extensive literature review was made to obtain a better insight on T2DM and the evolution of an SEM model for HRQoL data. This research involved three phases, which are the psychometric testing of the Malay versions of the Audit of Diabetes Dependent QoL (ADDQoL) and the Problem Areas in Diabetes Scale (PAID); modelling the HRQoL of T2DM patients and a simulation study. Firstly, a convenience sample of 309 T2DM outpatients were examined in the cross-sectional research phase. Confirmatory Factor Analysis (CFA) confirmed a three-factor solution of MY-PAID-20. Strong content validity and internal consistency reliability (Cronbach's a = 0.950) was demonstrated. A one-factor solution of the MY-ADDQoL which was similar to the original version was confirmed and internal consistency reliability was high (Cronbach's a = 0.945). In the second phase, the developed theoretical SEM was evaluated…